2021
DOI: 10.3390/fib9110068
|View full text |Cite
|
Sign up to set email alerts
|

Natural-Fibrous Lime-Based Mortar for the Rapid Retrofitting of Heritage Masonry Buildings

Abstract: The present work aims to define the mechanical behavior of a new composite material for the preservation and enhancement of the vast historical and architectural heritage particularly vulnerable to environmental and seismic actions. The new composite represents a novelty in the landscape of the fibrous mortars and consists of natural hydraulic lime (NHL)-based mortar, strengthened by Sisal short fibers randomly oriented in the mortar matrix. The developed mortar ensures the chemical-physical compatibility with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Trying new materials to innovate low-industrial construction techniques and lower costs is an exciting challenge for the construction industry. The earthquake-resistant effect of plant fibers on masonry buildings and the above two innovative characteristics have also been confirmed [38][39][40].…”
Section: Introductionmentioning
confidence: 66%
“…Trying new materials to innovate low-industrial construction techniques and lower costs is an exciting challenge for the construction industry. The earthquake-resistant effect of plant fibers on masonry buildings and the above two innovative characteristics have also been confirmed [38][39][40].…”
Section: Introductionmentioning
confidence: 66%
“…In this paper, the durability of hydraulic lime soil is improved by adding sodium methyl silicate, and the effect of sodium methyl silicate on its performance is studied, which provides a theoretical basis for the study of modified soil materials in the restoration and protection of earthen sites. Because the composite material has good mechanical properties and durability, it has wide application prospects in the restoration of soil sites and can be used to repair cracks, spalling, and other diseases of the walls of soil sites [21].…”
Section: Of 18mentioning
confidence: 99%
“…They concluded that sustainable materials can be used for masonry strengthening. Vailati, M.; Mercuri, M.; Angiolilli, M.; Gregori, [38] discussed the use of Sisal short fibers in lime-based mortar. Mortar samples were tested in three point bending assembly.…”
Section: Testing Procedures On Materialsmentioning
confidence: 99%